Human development in Iraq: Between structural improvement and persistent development gaps (an analytical reading of human development reports) - Hassan Abdullah Ahmed (Universitas Negeri Malang, 2026)
This research aims to determine the extent of people's participation in development, considering them both the means and the end, and to identify the most significant achievements in 2025 within the framework of human development in Iraq, based on the calculated index. According to the choices available to individuals, which are based on indicators (living a healthy and long life, acquiring education and knowledge, and enjoying a decent standard of living), Iraq was classified among the countries with high human development for 2025, after having consistently ranked in the middle of the indicators in reports for many years, despite the challenges facing these indicators.